Analysis of serum β-amyloid peptides, α2-macroglobulin, complement factor H, and clusterin levels in APP/PS1 transgenic mice during progression of Alzheimer's disease. Issue 15 (19th October 2016) - Wang, Dejiang; Di, Xiangjun; Fu, Lu; Li, Yingnan; Han, Xiao; Wu, Hui; Cai, Linjun; Meng, Xiangyu; Jiang, Chunlai; Kong, Wei; Su, Weiheng
Abstract : As a progressive age-related neurodegenerative disorder, Alzheimer's disease (AD) is a global health concern. Despite the availability of psychological testing, neuroimaging, genetic testing, and biochemical assays of cerebrospinal fluid, convenient and accurate blood biomarkers for the prediction, diagnosis, and preclinical studies of AD are still lacking. The present study aims to longitudinally evaluate the feasibility of β-amyloid proteins, α2-macroglobulin (α-2M), complement factor H (CFH), and clusterin as blood biomarkers of AD. Using APP/PS1 transgenic and wild-type mice, cognitive impairment and amyloid plaque counts in the brain were evaluated over a range of ages using the Morris water maze test and immunohistochemistry methods, respectively. Serum Aβ40, Aβ42, α-2M, CFH, and clusterin levels were measured by enzyme-linked immunosorbent assay and correlated with progression of AD. APP/PS1 transgenic mice presented progressive AD characteristics at the ages of 3, 6, 9, and 12 months. Serum Aβ42 levels and Aβ42/Aβ40 ratios increased significantly in transgenic 3- and 6-month-old mice compared with controls. Serum CFH levels decreased significantly in 3- and 6-month-old transgenic mice compared with controls. Meanwhile, serum clusterin levels increased significantly in 12-month-old transgenic mice compared with controls. The α-2M level was not significantly different between transgenic and wild-type mice. The APP/PS1 transgenic mouse is a model of familial AD. The present study indicated that the serum Aβ42 level, Aβ42/Aβ40 ratio, and CFH level are potential biomarkers in preclinical and early stages of AD, whereas serum clusterin level is a potential biomarker in the late stage of AD.